Wanderings in South America - Waterton, Charles, 1782-1865; Moore, Norman, 1847-1922 (Salt Lake City, UT : Project Gutenberg, 2010)
"Wanderings in South America" by Charles Waterton is a travel narrative written in the early 19th century. The book details the author's explorations of the lush and vibrant landscapes of South America, particularly focusing on the natural history and biodiversity he encountered. Waterton's keen observations on flora and fauna, as well as his encounters with various indigenous peoples, are central to the work, presenting a richly layered account of a world largely untouched by modernity. The opening of the narrative sets the stage for Waterton's journey, beginning in the town of Stabroek, where he embarks on an expedition through the forests of Demerara and Essequibo. He describes the challenges of navigating this verdant wilderness, including the exhausting heat and daunting swamp terrains. Waterton articulates his motivations for exploring the region, primarily his desire to collect wourali poison and learn about the indigenous cultures he encounters. This introductory section establishes the vibrant and sometimes perilous environment Waterton must traverse, blending engaging storytelling with scientific investigation into the natural world around him. (This is an automatically generated summary.)
Release date is 2010-03-28
This ebook was transcribed by Les Bowler
Keywords: Guyana -- Description and travel; Waterton, Charles, 1782-1865 -- Travel; Zoology -- Guyana; Pernambuco (Brazil) -- Description and travel; Antilles, Lesser -- Description and travel